Dexmedetomidine: present and future directions - Lee, Seongheon (Korean journal of anesthesiology, 2019)
Dexmedetomidine is a potent, highly selective α-2 adrenoceptor agonist, with sedative, analgesic, anxiolytic, sympatholytic, and opioid-sparing properties. Dexmedetomidine induces a unique sedative response, which shows an easy transition from sleep to wakefulness, thus allowing a patient to be cooperative and communicative when stimulated. Dexmedetomidine may produce less delirium than other sedatives or even prevent delirium. The analgesic effect of dexmedetomidine is not strong; however, it can be administered as a useful analgesic adjuvant. As an anesthetic adjuvant, dexmedetomidine decreases the need for opioids, inhalational anesthetics, and intravenous anesthetics. The sympatholytic effect of dexmedetomidine may provide stable hemodynamics during the perioperative period. Dexmedetomidine-induced cooperative sedation with minimal respiratory depression provides safe and acceptable conditions during neurosurgical procedures in awake patients and awake fiberoptic intubation. Despite the lack of pediatric labelling, dexmedetomidine has been widely studied for pediatric use in various applications. Most adverse events associated with dexmedetomidine occur during or shortly after a loading infusion. There are some case reports of dexmedetomidine-related cardiac arrest following severe bradycardia. Some extended applications of dexmedetomidine discussed in this review are promising, but still limited, and further research is required. The pharmacological properties and possible adverse effects of dexmedetomidine should be well understood by the anesthesiologist prior to use. Moreover, it is necessary to select patients carefully and to determine the appropriate dosage of dexmedetomidine to ensure patient safety.